Bowel Obstruction and Perforation as Emergency Presenting Sign of Colorectal Cancer with Peritoneal Carcinomatosis: A Case Report and Review - Randy Adiwinata; Linda Rotty; Michael Tendean; Bradley Jimmy Waleleng; Fandy Gosal; Luciana Rotty; Jeanne Winarta; Andrew Waleleng (The Indonesian Society for Digestive Endoscopy, 2020)
Colorectal cancer patient may present with variable clinical presentation. In few cases, colorectal cancer may present as emergency such as uncontrollable gastrointestinal bleeding, large bowel obstruction and in rarer fashion is bowel perforation. Worse prognosis is linked with emergency presenting colorectal cancer. Peritoneal carcinomatosis may occur in 10-35% of colorectal cancer patients and may develop bowel obstruction along with the primary colorectal cancer. Here, we report a-62-year-old man presented with large bowel obstruction leading to perforation without known history of colorectal cancer before. On emergency laparotomy, we found colorectal cancer and peritoneal carcinomatosis as the underlying cause. Prompt diagnosis and urgent management is warranted to improve the prognosis.